2019
DOI: 10.1177/1947603519870846
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of the Clinical Evidence on the Use of Autologous Matrix-Induced Chondrogenesis in the Knee

Abstract: Objective A systematic review and meta-analysis of Autologous Matrix-Induced Chondrogenesis (AMIC®) outcomes for grade III/IV chondral and osteochondral lesions of the knee treated with Chondro-Gide®. Design Studies with a minimum follow-up of 1 year providing clinical results of AMIC repair in the knee were included based on PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Methodological quality was assessed by the modified Coleman Methodology Score (mCMS). The meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 39 publications
0
26
1
2
Order By: Relevance
“…Our results are in accordance with the results of a recent AMIC meta-analysis based on 12 studies (11 level 4 studies and 1 level 1 study) that included a total of 375 patients. 37 Most patients were very satisfied with the result of the index procedure and would choose to undergo the same procedure again, if needed. This is in agreement with our previous reported results at midterm follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…Our results are in accordance with the results of a recent AMIC meta-analysis based on 12 studies (11 level 4 studies and 1 level 1 study) that included a total of 375 patients. 37 Most patients were very satisfied with the result of the index procedure and would choose to undergo the same procedure again, if needed. This is in agreement with our previous reported results at midterm follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…Microfracture, which is one of the most commonly performed surgical AC repair procedures, relies on the influx of MSCs from the surgically penetrated subchondral bone, to initiate (fibro-)cartilaginous repair [ 35 ] of small localized AC defects [ 31 ]. Moreover, MSCs are being used in an emerging clinical procedure termed “autologous matrix-induced chondrogenesis” (AMIC™), which, like microfracture, utilizes the influx of MSCs from the surgically penetrated subchondral bone, but in conjunction with administration of a collagen type I/III membrane [ 36 , 37 ].…”
Section: Clinical Use Of Chs and Mscs In Ac Repair Proceduresmentioning
confidence: 99%
“…The AMIC technique is a one-step procedure for the treatment of knee cartilage defects. Many authors have reported good or excellent clinical results at mid-term follow-up in the management of knee chondral defects [25].…”
Section: Discussionmentioning
confidence: 99%
“…Satisfactory results, in terms of pain reduction and functional improvement, have been already reported for up to 7 years [14,[18][19][20][21][22][23][24]. A very recent meta-analysis concerning the clinical evidence on the use of AMIC in the knee confirmed that it can be recommended for the treatment of knee chondral and osteochondral defects [25]. In particular, good outcomes were also demonstrated in patients presenting patellofemoral cartilage defects although at a short follow-up [26,27].…”
Section: Introductionmentioning
confidence: 95%